GAYA PENYUTRADARAAN FILM TUGAS AKHIR MAHASISWA JURUSAN FILM DAN TELEVISI - Rembulan, Dara Bunga (LAYAR: Jurnal Ilmiah Seni Media Rekam, 2017)
Student creativity in film making as a final project is increasing, various forms of narrative and cinematographic techniques are applied in the films made. Film is the easiest medium to disseminate any form of information. At the academic level, especially the Institut Seni Budaya Indonesia Bandung, documentary film becomes the final task of the academic learning stage. Documentary films are packaged in an interesting and have a moral message conveyed to the public. The number of graduates of film and television programs up to now amounts to 106 people with varying work character one of them is visible from the creation they created. This topic is very important to be appointed to know the characteristics of the director of the visual results in the work of Final Documentary Film Works by students of the Film and Television majors of the Indonesia Cultural Art Institut of Bandung (Institut Seni Kebudayaan Indonesia Bandung).This research uses qualitative research method to analyze the object under study, data obtained from literature study, observation of work and interview. Technical data analysis is done based on auteur theory, where the film can reflect the personality and creativity of a director. The results of this study show the variation of the directing style that influences the characters created in the final documentary work. Finallly this research can be used as a learning development and the development of innovative work creation with a variety of directorial styles.